Impact of Right Ventricular‐Pulmonary Circulation Coupling on Mortality in SARS‐CoV‐2 Infection - Francesca Bursi; Gloria Santangelo; Andrea Barbieri; Anna Maria Vella; Filippo Toriello; Federica Valli; Dario Sansalone; Stefano Carugo; Marco Guazzi (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The COVID‐19–related pulmonary effects may negatively impact pulmonary hemodynamics and right ventricular function. We examined the prognostic relevance of right ventricular function and right ventricular‐to‐pulmonary circulation coupling assessed by bedside echocardiography in patients hospitalized with COVID‐19 pneumonia and a large spectrum of disease independently of indices of pneumonia severity and left ventricular function. Methods and Results Consecutive COVID‐19 subjects who underwent full cardiac echocardiographic evaluation along with gas analyses and computed tomography scans were included in the study. Measurements were performed offline, and quantitative analyses were obtained by an operator blinded to the clinical data. We analyzed 133 patients (mean age 69±12 years, 57% men). During a mean hospital stay of 26±16 days, 35 patients (26%) died. The mean tricuspid annular plane systolic excursion/pulmonary artery systolic pressure (TAPSE/PASP) ratio was 0.48±0.18 mm/Hg in nonsurvivors and 0.72±0.32 mm/Hg in survivors (P=0.002). For each 0.1 mm/mm Hg increase in TAPSE/PASP, there was a 27% lower risk of in‐hospital death (hazard ratio [HR], 0.73 [95% CI, 0.59–0.89]; P=0.003). At multivariable analysis, TAPSE/PASP ratio remained a predictor of in‐hospital death after adjustments for age, oxygen partial pressure at arterial gas analysis/fraction of inspired oxygen, left ventricular ejection fraction, and computed tomography lung score. Receiver operating characteristic analysis was used to identify the cutoff value of the TAPSE/PASP ratio, which best specified high‐risk from lower‐risk patients. The best cutoff for predicting in‐hospital mortality was TAPSE/PASP <0.57 mm/mm Hg (75% sensitivity and 70% specificity) and was associated with a >4‐fold increased risk of in‐hospital death (HR, 4.8 [95% CI, 1.7–13.1]; P=0.007). Conclusions In patients hospitalized with COVID‐19 pneumonia, the assessment of right ventricular to pulmonary circulation coupling appears central to disease evolution and prediction of events. TAPSE/PASP ratio plays a mainstay role as prognostic determinant beyond markers of lung injury.